2014
DOI: 10.1074/mcp.m114.040113
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Synaptic Pathology with a Novel Affinity Mass Spectrometry Approach

Abstract: We report a novel strategy for studying synaptic pathology by concurrently measuring levels of four SNARE complex proteins from individual brain tissue samples. This method combines affinity purification and mass spectrometry and can be applied directly for studies of SNARE complex proteins in multiple species or modified to target other key elements in neuronal function. We use the technique to demonstrate altered levels of presynaptic proteins in Alzheimer disease patients and prion-infected mice. Molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…A possible explanation for this finding could be that STX1A levels undergo a compensatory increase in these regions (possibly via increased collateral branching or sprouting) in order to compensate for the reduced input that dentate granule cells receive from the EC layer II, which is evident by the reduced STX1A level in the OML. As opposed to our findings, in a few proteomics study, decreased levels of STX1A were reported in AD brains [7, 32, 58]. However, these studies have used homogenates prepared from bulk tissue of AD brains, and would not be able to tease out cell- and layer-specific discrete changes as the ones observed in sub-hippocampal regions in the current study.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for this finding could be that STX1A levels undergo a compensatory increase in these regions (possibly via increased collateral branching or sprouting) in order to compensate for the reduced input that dentate granule cells receive from the EC layer II, which is evident by the reduced STX1A level in the OML. As opposed to our findings, in a few proteomics study, decreased levels of STX1A were reported in AD brains [7, 32, 58]. However, these studies have used homogenates prepared from bulk tissue of AD brains, and would not be able to tease out cell- and layer-specific discrete changes as the ones observed in sub-hippocampal regions in the current study.…”
Section: Discussioncontrasting
confidence: 92%
“…Although decreased mRNA and/or protein levels of these five presynaptic markers have been previously detected in AD brain [4, 7, 32, 51], these studies have so far been performed on homogenates prepared from cortical or hippocampal bulk tissue, thus not allowing any detailed examination of different hippocampal sub-regions. Here, we investigated the distribution of presynaptic proteins in 10 hippocampal sub-regions of AD and control cases using immunofluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, differential diagnosis between AD and other forms of dementia is frequently difficult. Early loss of synaptic function is believed to play an important role in AD and recently the CSF levels of peptide products from both presynaptic and postsynaptic proteins have been shown to be altered in AD. Moreover, inflammatory processes and oxidative stress may be involved in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In this report a MS and MS/MS resolution setting of 70,000, at 200 m / z , was used. Recently we have developed a similar PRM method targeting synaptic pathology by measuring the relative amount of the SNARE complex protein synaptosomal-associated protein 25 (SNAP-25) in human CSF and brain tissue [ 35 , 36 ]. This highlights the potential of PRM methods in neurobiological biomarker discovery and development.…”
Section: Discussionmentioning
confidence: 99%